Adverse Effects of Anti-PD-1/PD-L1 Therapy in Non-small Cell Lung Cancer - Su, Chaoyue; Wang, Hui; Liu, Yunru; Guo, Qiaoru; Zhang, Lingling; Li, Jiajun; Zhou, Wenmin; Yan, Yanyan; Zhou, Xinke; Zhang, Jianye (Frontiers in Oncology, 2020)
Currently, immunotherapy has shown great efficacy in clinical trials, and monoclonal antibodies directed against immune checkpoint PD-1/PD-L1 have shown encouraging results in first-line or second-line treatment of non-small cell lung cancer patients. Meanwhile, anti-PD-1/PD-L1 immune checkpoint drugs combined with other treatments, such as chemotherapy, targeted therapy as well as anti-CTLA-4 checkpoint therapy, are considered an attractive treatment with higher efficacy. However, toxicity associated with PD-1/PD-L1 blockade is worth attention. Understanding the adverse effects caused by anti-PD-1/PD-L1 immunosuppressive agents is vital to guide the clinical rational use of drug. In this review, we summarized the adverse effects that occurred during the clinical use of anti-PD-1/PD-L1 inhibitors in the treatment of non-small cell lung cancer and discussed how to effectively manage and respond to these adverse reactions.